The effect of incentive return-to-work policies on single-parent families: A comparative approach - Amine, Samir; Ouattara, Pénayori (The European Journal of Applied Economics, 2015)
As part of their struggle against inequality and social exclusion, many countries are trying to reform their redistributive system and low-income support measures to encourage return to work, and reduce inactivity traps. The purpose of this article is to propose a reflection on the social and fiscal policies. The analysis focuses on three measures in three different countries: the Earned Income Tax Credit (EITC) in the United States, the Working Tax Credit (WTC) in the UK and the Active Solidarity Income (RSA) in France. The emphasis is placed on the effects of such policies on the situation of single parents, in particular as part of their transition from welfare (social assistance) to the labor market.